PREDICTORS OF THE STUDENTS' ENGLISH ACHIEVEMENT AT LOWER SECONDARY SCHOOL: CLIL CONTEXT - Rachmajanti, Sri; Anugerahwati, Mirjam (TEFLIN Journal, 2019)
English across curriculum has been of world-wide practice, including in Indonesia. Through a blended curriculum (a synergy of national and international frameworks), some schools have put this program into action within the context of CLIL (Content-Language Integrated Learning). This correlational study is intended to find out the correlation between a combination of predictor variables and students' English learning achievement in secondary school in CLIL context. The predictors include the students' interest in ELT, the students' internal and external motivation, the facilities, the exposure to English, and the interactional process between teacher and students at primary school level. The study also investigates to what extent the predictors, in combination as well as individually, contribute to students' English learning achievement in secondary school in CLIL context. Data were collected through questionnaires administered to four secondary schools which implement an international framework. Seventy students were the sample of the present study. The data were analyzed using multiple regression. Results show that the two most significant predictors of the students' English achievement in secondary school are the students' interest and the school facilities.